A Hospital Management System Suitable for Every Hospital as a Solution to the Problems of the Hospital Industry in Sri Lanka - Ihalagedara, I.H.U.B.; Ranasinghe, R.A.D.M.; Waththaladeniya, N.M.; Samarakoon, S.M.A.D.; De Silva, D.I.; De Zoysa, R.R.P. (International Journal of Engineering and Management Research, 2022)
This paper is based on the concept of creating a management system for a hospital, related functionalities and other learning of it in order to make the process efficient, fast and safe. This study aids in increasing the productivity of a hospital by decreasing the time wastage which was identified with the manual process. The system is proposed after identifying the problems in patients and the hospital staff to cover areas of human resources, marketing and finance. One of the main goals is to provide a system which can automate a manual process that is used in day-to-day life. The proposed system which is known as “Hospital MS” is a web application which contains the necessary functionalities of the stakeholders of this system. Mainly this system can manage the patient, doctors, recipients, lab assistant and the system administrator to maintain and manage the system. Since we can provide a platform to every person who is interacting with this system, there are lots of advantages for everyone. Another aim of this system is to provide the patient with a way of interacting with the hospital. With this proposed system a particular patient can make the appointments to a doctor, and once the appointment is completed, the patient can keep the interaction with the doctor by sharing information like prescriptions. One of the other concerns that this system is going to look after is the centralized database to manipulate the data in a more reliable and efficient way.